Genealogy of Thought of Islamic Da'wah Organizations in Indonesia: A Historical Analysis of NU, Muhammadiyah, Persis, and Al-Washliyah - Ummi Sa'adah; Ekki Suryana Zaen; Muhammad Firdaus; M Yakub (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
This article examines the genealogy of thought of four major Islamic da'wah institutions in Indonesia, Nahdlatul Ulama (NU), Muhammadiyah, Persatuan Islam (Persis), and Al-Jam'iyatul Washliyah (Al-Washliyah). Employing a historical-comparative approach with genealogical analysis inspired by Michel Foucault's framework, this study traces the historical roots, ideological foundations, da'wah character, and intellectual dynamics of each institution within the context of modern Indonesia. Data were gathered through primary and secondary academic literature from leading scholars in the field of Indonesian Islamic history. The findings reveal that although all four institutions emerged from relatively similar socio-historical pressures namely Dutch colonialism and the global wave of Islamic modernism, each developed a distinctive da'wah character. NU embraced a cultural-traditionalist approach rooted in the pesantren tradition and the Ahlussunnah wal Jamaah creed, Muhammadiyah championed dakwah bil-hal (action-based preaching) and social reformism through modern education and charitable enterprises, Persis emphasized textual-puritan argumentation by rejecting taqlid and bid'ah, while Al-Washliyah integrated da'wah with education within a wasathiyyah (moderate) framework. These differing orientations can be traced to divergent intellectual genealogies, Muhammadiyah and Persis absorbed reformist thought from the Middle East (al-Afghani, Abduh, Ridha), while NU and Al-Washliyah remained more deeply rooted in the classical Islamic scholarly tradition of the Malay-Nusantara world. This diversity of orientation represents not a contradiction but rather the intellectual richness of Indonesian Islam, a complementary plurality capable of addressing contemporary challenges including digitalization and religious radicalism